Časovno odvisno vedenje pogonskih jermenov pod vplivom periodične mehanske obremenitve - Zupančič, Barbara (Strojniški vestnik, 2007)
A drive belt's durability is a critical factor for the sustainable operation of engines. Thus, understanding the mechanisms that affect their durability is extremely important. In this paper we present the continuation of our research on the time-dependent behavior of dynamically loaded elastomeric products. For this purpose the constitutve model has been developed, which made possible the analyses of the stress-strain state 1. The development of the costitutive model is based on the modelling of the transmission belts when exposed to tooth-like periodic mechanical loading during the operation of the engine. Within each loading cycle the elastomeric material undergoes a combination of creep and the retardation process. Under certain conditions, defined by the drive beltćs geometry and the pulleys' angular velocity, the retardation process between two loadings cannot be fully completed to a strain-free state. Consequently, the strain state starts to accumulate, which leads to hardening of the material, crack formation, and ultimately to the failure of the belt. he results have shown that there exists some critical loading conditions for the strain-accumulation process to occur. We can predict that the product will almost certainly fail if it operates under critical conditions, which depend on the retardation time (location of the spectrum). The magnitude of the accumulated strain is dictated by the intensity of the spectrum line. Thus, the mechanical spectrum of the polymeric material, from which the product is made, is the most important material function for predicting the durability of the polymeric product. In this paper we analyze the effect of the location of a single spectrum line on the critical operating conditions. We found that longer response times for a material mean lower critical operating angular velocities.
Keywords: jermeni; deformacije; modeli; analize